Risk Factors for COVID‐19 and Rheumatic Disease Flare in a US Cohort of Latino Patients. Issue 7 (28th May 2021) - Fike, Alice; Hartman, Julia; Redmond, Christopher; Williams, Sandra G.; Ruiz‐Perdomo, Yanira; Chu, Jun; Hasni, Sarfaraz; Ward, Michael M.; Katz, James D.; Gourh, Pravitt
Abstract : Objective: Latino patients are overrepresented among cases of coronavirus disease 2019 (COVID‐19) and are at an increased risk of severe disease. Prevalence of COVID‐19 in Latinos with rheumatic diseases is poorly reported. This study was undertaken to characterize COVID‐19 clinical features and outcomes in Latino patients with rheumatic diseases. Methods: We conducted a retrospective study of Latino patients with rheumatic diseases from an existing observational cohort in the Washington, DC area. Patients seen between April 1, 2020 and October 15, 2020 were analyzed in this study. We reviewed demographic characteristics, body mass index (BMI), comorbidities, and use of immunomodulatory therapies. An exploratory classification and regression tree (CART) analysis along with logistic regression analyses were performed to identify risk factors for COVID‐19 and rheumatic disease flare. Results: Of 178 Latino patients with rheumatic diseases, 32 (18%) were identified as having COVID‐19, and the incidence rate of infection was found to be 3‐fold higher than in the general Latino population. No patients required intensive care unit–level care. A CART analysis and multivariable logistic regression analysis identified a BMI of >30.35 as a risk factor for COVID‐19 (odds ratio [OR] 3.37 [95% confidence interval (95% CI) 1.5–7.7]; P = 0.004). COVID‐19 positivity was a risk factor for rheumatic disease flare (OR 4.57 [95% CI 1.2–17.4]; P = 0.02). Conclusion: Our findings indicate that Latino patients with rheumatic diseases have a higher rate of COVID‐19 compared with the general Latino population. Obesity is a risk factor for COVID‐19, and COVID‐19 is a risk factor for rheumatic disease flare. Latino patients with risk factors should be closely followed up, especially post–COVID‐19 in anticipation of disease flare.